Additive Inhibition of Reflex Bladder Activity Induced by Bilateral Pudendal Neuromodulation in Cats - Shapiro, Katherine; Pace, Natalie; Morgan, Tara; Cai, Haotian; Shen, Bing; Wang, Jicheng; Roppolo, James R.; de Groat, William C.; Tai, Changfeng (Frontiers in Neuroscience, 2020)
Objective: To determine the inhibitory effect on bladder activity induced by bilateral pudendal neuromodulation. Methods: In 10 cats under anesthesia, two tripolar cuff electrodes were implanted bilaterally on the pudendal nerves for stimulation. A double lumen catheter was inserted into the bladder through the urethra to infuse saline and measure bladder pressure. During repeated cystometrograms (CMGs) pudendal nerve stimulation (PNS: 5 Hz, 0.2 ms, 5-15 minutes) was applied unilaterally or bilaterally at 1- or 2-times intensity threshold (T) for inducing anal sphincter twitching. PNS inhibition was indicated by the increase in bladder capacity measured by CMGs. Results: Unilateral PNS at 1T did not significantly increase bladder capacity, but at 2T significantly (p<0.05) increased bladder capacity by about 30%. Bilateral PNS at 1T also failed to increase bladder capacity, but at 2T significantly (p<0.05) increased bladder capacity by about 60%, indicating an additive effect induced by the bilateral 2T PNS. Unilateral 1T PNS did not enhance the inhibitory effect induced by contra-lateral 2T PNS. Conclusions: This study in anesthetized cats reveals that an additive inhibition of reflex bladder activity can be induced by bilateral pudendal neuromodulation, indicating that bilateral PNS might achieve better therapeutic efficacy in treating OAB than unilateral PNS.